Divorce and Severity of Coronary Artery Disease: A Multicenter Study. (24th July 2017) - Daoulah, Amin; Al-Murayeh, Mushabab; Al-kaabi, Salem; Lotfi, Amir; Elkhateeb, Osama E.; Al-Faifi, Salem M.; Alqahtani, Saleh; Stewart, James; Heavey, Jon; Hurley, William T.; Alama, Mohamed N.; Faden, Mazen; et al.
Abstract : The association between marital status and coronary artery disease (CAD) is supported by numerous epidemiological studies. While divorce may have an adverse effect on cardiac outcomes, the relationship between divorce and severe CAD is unclear. We conducted a multicenter, observational study of consecutive patients undergoing coronary angiography during the period between April 1, 2013, and March 30, 2014. Of 1, 068 patients, 124 (12%) were divorced. Divorce was more frequent among women (27%) compared to men (6%). Most divorced patients had been divorced only once (49%), but a subset had been divorced 2 (38%) or ≥3 (12%) times. After adjusting for baseline differences, there was no significant association between divorce and severe CAD in men. In women, there was a significant adjusted association between divorce and severe MVD (OR 2.31 [1.16, 4.59]) or LMD (OR 5.91 [2.19, 15.99]). The modification of the association between divorce and severe CAD by gender was statistically significant for severe LMD (P i n t e r a c t i o n 0.0008) and marginally significant for CAD (P i n t e r a c t i o n 0.05). Among women, there was a significant adjusted association between number of divorces and severe CAD (OR 2.4 [95% CI 1.2, 4.5]), MVD (OR 2.0 [95% CI 1.4, 3.0]), and LMD (OR 3.4 [95% CI 1.9, 5.9]). In conclusion, divorce, particularly multiple divorces, is associated with severe CAD, MVD, and LMD in women but not in men.